2018
DOI: 10.1016/j.bbadis.2017.12.038
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of insulin-sensitive glucose transporters during insulin resistance-induced atrial fibrillation

Abstract: Diabetes has been identified as major risk factor for atrial fibrillation (AF). Although glucose and insulin disturbances during diabetes may affect atrial function, little is known about the potential pathogenic role of glucose metabolism during AF. Glucose transport into the cell via glucose transporters (GLUTs) is the rate-limiting step of glucose utilization. Although GLUT4 is the major isoform, GLUT8 has emerged as a novel insulin-sensitive cardiac isoform. We hypothesized that atrial glucose homeostasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
48
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 49 publications
4
48
1
Order By: Relevance
“…Similarly, severe hypoglycemia-induced fatal cardiac arrhythmias were enhanced in diabetic rats with insulin deficiency (14). Recently, we demonstrated that long term high-fat diet-induced insulin resistance enhanced the vulnerability of AF induction in a rodent model (15). Taken together, the results of these studies suggest that disturbances in glucose and insulin could enhance the arrhythmogenicity of the atrium, which contains the pacemaker of the heart, potentially leading to AF (6,9,16).…”
Section: Introductionmentioning
confidence: 82%
“…Similarly, severe hypoglycemia-induced fatal cardiac arrhythmias were enhanced in diabetic rats with insulin deficiency (14). Recently, we demonstrated that long term high-fat diet-induced insulin resistance enhanced the vulnerability of AF induction in a rodent model (15). Taken together, the results of these studies suggest that disturbances in glucose and insulin could enhance the arrhythmogenicity of the atrium, which contains the pacemaker of the heart, potentially leading to AF (6,9,16).…”
Section: Introductionmentioning
confidence: 82%
“…Maria et al reported that insulin‐resistant mice were vulnerable, and had a propensity, to both induced and spontaneous AF. In the present study, LA conduction velocity was significantly slower in the insulin‐resistant group than in the normal group.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance, which is a state of decrease in insulin response, is well known to be the underlying mechanism in the development of the abnormal glucose metabolism . There are limited data about the relationship between the pathogenesis of AF and insulin resistance . In addition, it remains unclear whether insulin resistance affects AF recurrence after PVI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin resistance induces both atrial structural remodeling and abnormal intracellular calcium homeostasis, contributing to increased AF susceptibility [37]. It is reported that insulin resistance-induced AF was associated with impairment in the trafficking and expression of the major cardiac isoform GLUT4 and the novel isoform GLUT8 [38]. Inflammatory markers IL-6 and TNF play an essential role in the occurrence and development of AF.…”
mentioning
confidence: 99%